O trabalho docente em dança: uma análise crítica desde a formação profissional à atuação na educação básica - Boaventura, Michelle Aparecida Gabrielli (2021)
The present work has as main objective the compreehension of reality of dance teachers of municipal schools of basic education from João Pessoa – PB, verifying his insertion and permanence on his acting realm, as well his practices and work conditions, as from an approaching that can be problematical, critic and dialogical. As from tesis’ hypothesis that the ignorance of dance as a profession from college degree constitutes itself in one of the elements of work’s precarious conditions of dance teacher inset on basic education. The thesis was developed through qualitative research characterizing itself as explanatory once that was sought identify the factors that contributes to dancer teach from formal schools can be unstable in his workplace. The research has it base on Hitorical-Dialetical Materialism, which utilized the dialetical method to make the analisys of results. The data production took place from semistructured interview, and from the application of a form about the socioeconomic profile from participants teachers and an open survey. The individuals of this research were 11 (eleven) dance teachers that teach to the Childhood Ecucation, Basic Education and Education of Young and Adults chosen from the criterion of have joined on municipal teaching public network in 2015 through public service exam achieve by the municipal government of João Pessoa - PB for posts on Secretary of Ecucation and Culture (Rescript nº 01, of november 08/2013). The discovered results demonstrate that when considering the dialogical and humanist perspective from Popular Education along the dance teacher’s view from basic education, the comprehension of any formal educative act demands thinking as an active individual and that from the actuation of each one of them, scenarios of competition for social control has been built. Such considerations underlies and qualifies the educational work, and here is included the dance teacher, seeing that his insertion and permanence on work posts are configured as power disputes and the unstability of work conditions denotes the world perspective that one has, but also the world that one desires to aim, having the humanizing of this spaces as a focus to be achieve.